Implementation of Telegram Notification System for Motorbike Accidents Based on Internet Of Things - Setiawan, I Putu Edi; Desnanjaya, I Gusti Made Ngurah; Supartha, Kadek Dwi Gandika; Ariana, A.A Gede Bagus; Putra, I Dewa Putu Gede Wiyata (Yayasan Sraddha Panca Widya Nusantara, 2024)
In making this final project, it describes in detail the process of designing and building a telegram notification system for motorcycle accidents based on the internet of things. Before designing and building the system, a survey was conducted using the questionnaire and interview methods as the basis for the benchmark in designing and building the system. The purpose of this final project is to design and build a telegram notification system for motorcycle accidents based on the internet of things which is used to make it easier to obtain information when an accident occurs in a quiet place or an area that is common to motorists. The telegram notification system for motorcycle accidents has the main component, namely ESP32 as a microcontroller that can be connected to wifi, the accident detector of this system uses the MPU6050 sensor. The results of this final project, the system can run as expected, at the stage of testing the difference in the GPS comparison obtained can be categorized as successful, and the slope ratio has a difference that is almost the same as the standard clinometer tool, then the comparison of the A3144 sensor there is a difference obtained with the standard tachometer tool. And the system can send notifications when a motorcycle has an accident and the system is able to send information when Telegram users need it.